Robot-assisted resection of choledochal cyst in children - Jin, Yi; Zhang, Shuhao; Cai, Duote; Zhang, Yuebin; Luo, Wenjuan; Chen, Ken; Chen, Qingjiang; Gao, Zhigang (Frontiers in Pediatrics, 2023)
Background: The emergence of the robotic surgery system has assisted the further development of minimally invasive surgery by facilitating more delicate and precise complex procedures. The purpose of this study was to present a study of robot-assisted resection of the choledochal cyst and to discuss the technical points. Methods: In total, 133 patients who were diagnosed with a choledochal cyst and underwent surgery from April 2020 to February 2022 in the Children's Hospital, Zhejiang University School of Medicine, were retrospectively analyzed. The data were collected including the clinical information of the patients, operative details, and postoperative outcomes. Results: Among these 133 patients, 99 underwent robot-assisted surgery and 34 underwent laparoscopic assisted surgery. The median operation time was 180 mins, with an interquartile range (IQR) of 170 to 210 mins for the robot-assisted group and 180 mins with an IQR of 157.5 to 220 mins in the laparoscopic assisted group (P = 0.290). The detection rate of 82.5% for the distal opening of the cystic type of choledochal cyst was higher in the robot-assisted group than that in the laparoscopic assisted group at 34.8% (P = 0.000). The postoperative hospital stay was shorter (P = 0.009) and the hospitalization expense was higher (P = 0.000) in the robot-assisted group than that of the laparoscopic assisted group. There was no significant difference between the two groups in terms of complications, postoperative indwelling days of the abdominal drainage tube, intraoperative blood loss, and postoperative fasting time (P > 0.05). Conclusions: Robot-assisted resection of choledochal cyst is safe and feasible, it is ideal for the patient requiring a meticulous operation and its postoperative recovery was shorter than for traditional laparoscopy.